Two new species of Begonia (Begoniaceae) from Borneo - Ardi, Wisnu Handoyo; Girmansyah, Deden; Lin, Che-Wei; Hughes, Mark (Phytotaxa, 2019)
Two new species of Begonia, B. inggitiae and B. dracopelta, are described from Borneo. Begonia inggitiae is endemic to Kalimantan, and B. dracopelta is found in both Kalimantan and Sarawak, and both belong to Begonia section Petermannia.